Empowering Women Farmers' Groups as an Emancipation Strategy: Challenging Poverty and Achieving Food Independence in the Green Economy Era - Kurniawan, Edhy; Israyani, Nur; Triadi, Feby; Faidzaturrahmah, Nur; A, M Awaluddin (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
This study aims to analyze the role of Kelompok Wanita Tani (KWT) in alleviating poverty and achieving food self-sufficiency in Lampoko Village, Barebbo District, Bone Regency, and to identify barriers and effective empowerment strategies. The study used a qualitative approach with a case study method, involving in-depth interviews, participant observation, and documentation of KWT activities. The results indicate that KWT plays a strategic role in household food security through the use of yards as production spaces and strengthening social solidarity among members. However, KWT faces various technical, structural, and social barriers, including limited land, capital, agricultural knowledge and technology, organizational management, women's double burden, limited market access, and minimal institutional support. This study recommends an integrated empowerment strategy that includes increasing access to resources, strengthening technical and managerial capacity, reducing the burden of dual roles, developing market access, and strengthening institutional support to ensure program sustainability. Implementation of this strategy is expected to expand women's agency, improve family welfare, strengthen food self-sufficiency, and affirm KWT's position as a strategic actor in village development.